Role of Tumor Necrosis Factor Alpha and Transforming Growth Factor Beta as Predictive Marker for Psoriasis Patients - H Adbullah , Tadamun; I Latif, Ismail; Kh Ibrahim , Khudair (Diyala Journal of Medicine, 2020)
Background: Psoriasis is a multifactorial and inflammatory skin disease. The etiology is not well. A large number of cytokines have been shown to be elevated in serum concentration and psoriatic lesion, and the elevation is correlate with psoriasis severity. Objective: To evaluate TNF-a and TGF-B1 index in psoriasis which could help as predictive marker of severity of psoriasis in Baquba teaching hospital Iraq. Patients and Methods: Forty nine patients with psoriasis (27male and 22 female) were included in this study . Their age range between (7-70) years old. The study was performed in Baquba Teaching Hospital during period from December 2018 to June 2019. Each case was diagnosed by Dermatologist. Results: In our study we compare the mean, standard deviation and P. value of TNF-a and TGF-B in patients of psoriasis. We have found that psoriasis patients have a highly significant difference compared to controls(P=0.001) in both genders. Conclusion: This study concludes a significant association between tumor necrosis factor alpha and transforming growth factor beta-1 in psoriasis patients in both gender.